Desmin Aggregate Formation by R120G αB-Crystallin Is Caused by Altered Filament Interactions and Is Dependent upon Network Status in Cells - Der Perng, Ming (The American Society for Cell Biology, 2004)
The R120G mutation in αB-crystallin causes desmin-related myopathy. There have been a number of mechanisms proposed to explain the disease process, from altered protein processing to loss of chaperone function. Here, we show that the mutation alters the in vitro binding characteristics of αB-crystallin for desmin filaments. The apparent dissociation constant of R120G αB-crystallin was decreased while the binding capacity was increased significantly and as a result, desmin filaments aggregated. These data suggest that the characteristic desmin aggregates seen as part of the disease histopathology can be caused by a direct, but altered interaction of R120G αB-crystallin with desmin filaments. Transfection studies show that desmin networks in different cell backgrounds are not equally affected. Desmin networks are most vulnerable when they are being made de novo and not when they are already established. Our data also clearly demonstrate the beneficial role of wild-type αB-crystallin in the formation of desmin filament networks. Collectively, our data suggest that R120G αB-crystallin directly promotes desmin filament aggregation, although this gain of a function can be repressed by some cell situations. Such circumstances in muscle could explain the late onset characteristic of the myopathies caused by mutations in αB-crystallin.